Morphological Changes of the Spleen with Polypragmasia - Akmal Abdullaevich Saidov (Universitas Muhammadiyah Sidoarjo, 2022)
The study was conducted on 100 white random-bred rats of newborns, three and six months old. Animals were taken out of the experiment at 3 months of age by instantaneous decapitation of animals under ether anesthesia. After opening the abdominal cavity, macroscopic changes in the spleen were studied. Using a caliper, the anatomical parameters of the extracted spleen were measured. The spleen was fixed in Carnoy's solution for further study. Treatment with no steroidal drugs showed damage to the lymphoid tissue of the spleen, structural changes in the pulp and a decrease in the mass of the spleen.